Human impact: Plastic pollution - Maric, Filip; Poto, Margherita; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To comprehend that plastic pollution is a major problem and is having an impact on oceans everywhere. These impacts are seen on beaches and shorelines and all the way to the deepest places in the ocean. Learning objectives: In this activity, pupils will gain an appreciation for the extent of plastic pollution in and around oceans. They will start to understand how plastic pollution can have a negative impact on life below the surface of the sea. Key words: Ocean pollution, plastics, microplastics.